Innovation in Greece: Technology Parks - Ταμπάκη, Μαρία (Πανεπιστήμιο Πελοποννήσου, 2022)
Through this thesis the aim is to highlight that the Science and Technology Parks of Greece even though they are small compared to the Technology Parks of the other countries, can promote innovation and "build up" a business from scratch. The International Association of Science Parks states that Technology Park is an organism that is made up of appropriately specialized personnel and has all the resources to be able to develop the businesses located within it. The community follows a culture of innovation and know-how and aims to make the businesses inside the incubators competitive and recognizable in the business world. A new product can be producted. Α new product can be produced through innovation. This product is created from the diversity of ideas and technologies that will be applied. The main characteristics of a Science and Technology Park are: a) cooperation with suitably qualified personnel, b) cooperation with Universities, c) the creation of businesses from the beginning to their full development, d) the support of the business by any technological means, e) tries to give a competitive advantage to the business, f) positively affects the macroeconomic environment of the business (knows about grants), g) it aims to increase productivity, h) it has the know-how and immediately realizes the impact of a small innovation, i) it supports the business from the simplest infrastructure to networking with research centers and j) it has excellent consulting capacity. Because of their partnerships with research centers and organizations, they can provide start ups with information on artificial intelligence, telecommunications, nanotechnology, health sciences and sustainable energy, as climate change affects people's livelihoods more than ever.
Η Καινοτομία στην Ελλάδα: Τεχνολογικά Πάρκα
Keywords: Θερμοκοιτίδες επιχειρήσεων; Βιομηχανίες - Τεχνολογικές καινοτομίες; Επιχειρήσεις - Τεχνολογικές καινοτομίες; Βιομηχανικό μάνατζμεντ - Τεχνολογικές καινοτομίες; Επιχειρηματικότητα; Τεχνολογικές καινοτομίες - Διοίκηση και οργάνωση; Business incubators; Industries - Technological innovations; Business - Technological innovations; Industrial management - Technological innovations; Entrepreneurship; Technological innovations - Management; Technological Parks; Innovation; Incubator; Universities; Τεχνολογικά Πάρκα; Καινοτομία; Θερμοκοιτίδα; Πανεπιστήμια